High mobility group box 1 acts as an adjuvant for tuberculosis subunit vaccines. Issue 1 (May 2014) - Grover, Ajay; Troudt, Jolynn; Foster, Chad; Basaraba, Randall; Izzo, Angelo
Summary In order to ensure an ample supply of quality candidate tuberculosis (TB) subunit vaccines for clinical trials, it is imperative to develop new immunostimulatory adjuvants. High Mobility Box Group 1 (HMGB1), a member of the alarmin group of immunostimulatory proteins, is released by antigen‐presenting cells under various conditions and has been shown to induce T helper type 1 cytokines. We report that HMGB1 is effective as an adjuvant to enhance the protective efficacy and cellular immune response of TB subunit vaccines and that it is not dependent on the interaction between HMGB1 and receptor for advanced glycation end products, a major receptor for HMGB1. In the mouse model of TB, HMGB1 protein, when formulated with dioctadecylammonium bromide and 6000 MW early secretory antigenic target (ESAT‐6), was protective as a subunit vaccine but did not protect as molecular adjuvant in an ESAT‐6‐based DNA formulation. We then evaluated the immunoprophylactic and protective potential of a fusion protein of HMGB1 and ESAT‐6. The HMGB1–ESAT‐6 fusion protein induced strong antigen‐specific T helper type 1 cytokines at 30 days post‐immunization. The fusion protein vaccine enhanced activated and effector memory CD4 and CD8 T‐cell responses in the lungs and spleens of mice at 80 days post vaccination. Vaccination with the HMGB1–ESAT‐6 fusion protein also resulted in elevated numbers of poly‐functional CD4 T cells co‐expressing interleukin‐2, interferon‐γ and tumour necrosis factor‐α. The potent cell‐mediated immune response generated by the fusion protein correlated with protection against subsequent challenge with Mycobacterium tuberculosis in the mouse TB model.